Cytosolic Calreticulin Inhibits Microwave Radiation‐Induced Microvascular Endothelial Cell Injury Through the Integrin‐Focal Adhesion Kinase Pathway. (November 2014) - Xu, Fei‐Fei; Tao, Tian‐Qi; Wang, Xiao‐Reng; Li, Yu‐Zhen; Song, Dan‐Dan; Liu, Mi; Liu, Xiu‐Hua
Abstract Objective To determine the effects of cytosolic CRT on MR‐induced MMEC injury, and the underlying mechanism. Methods MMECs were randomized into eight groups: control, AdCRT (infected with pAdCMV/V5‐DEST‐CRT adenovirus), stCRT (transfected with rCRT‐siRNAs), Mock (transfected with scrambled siRNAs), MR (exposed to MR for six minutes), AdCRT + MR, stCRT + MR, and Mock + MR. The magnitude of cell injury were assessed by Annexin V‐PI staining, LDH activity in culture medium, MMEC migration ability, ultrastructure and cytoskeletal stability. Subcellular colocalization of CRT and ConA or integrin were evaluated by immunocytochemistry. The mRNA and protein expression levels of target genes were examined by qRT‐PCR and western blotting, respectively. Results MR‐induced cytotoxicity was dose‐dependent. Overexpression of cytosolic CRT suppressed MR injury, shown as decreased cell apoptosis, reduced LDH activity, enhanced cell migration capability, and maintenance of ultrastructure and cytoskeleton integrity. Conversely, CRT deficiency aggravated MR‐induced injury. Exposure of AdCRT MMECs to MR promoted membrane translocation of CRT and the interaction of CRT‐integrin‐α. Correlation analysis revealed that integrin‐α expression or FAK phosphorylation was positively associated with cytosolic CRT expression. Conclusions Cytosolic CRT inhibits MR‐induced MMEC injury through activation of the integrin‐FAK pathway.